2012
DOI: 10.1021/ja210837b
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Oxidized Welwitindolinones and (−)-N-Methylwelwitindolinone C Isonitrile

Abstract: We report the total synthesis of (–)-Nmethylwelwitindolinone C isonitrile, in addition to the total syntheses of the 3-hydroxylated welwitindolinones. Our routes to these elusive natural products feature the strategic use of a deuterium kinetic isotope effect to improve the efficiency of a late-stage nitrene insertion reaction. We also provide a computational prediction for the stereochemical configuration at C3 of the hydroxylated welwitindolinones, which was confirmed by experimental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(82 citation statements)
references
References 52 publications
3
74
0
2
Order By: Relevance
“…Furthermore, the aerobic oxidation of 146 and 148 under basic conditions provided C3-hydroxylated 147 and 149, respectively (Scheme 43). 75 The enantiospecic synthesis of (+)-N-methylwelwitindolinone D isonitrile (150) was achieved using the known tetracyclic intermediate 159. Cyclic carbamate 160 was assembled via oxidation of the indole ring followed by an intramolecular nitrene insertion reaction.…”
Section: Non-tryptaminesmentioning
confidence: 99%
“…Furthermore, the aerobic oxidation of 146 and 148 under basic conditions provided C3-hydroxylated 147 and 149, respectively (Scheme 43). 75 The enantiospecic synthesis of (+)-N-methylwelwitindolinone D isonitrile (150) was achieved using the known tetracyclic intermediate 159. Cyclic carbamate 160 was assembled via oxidation of the indole ring followed by an intramolecular nitrene insertion reaction.…”
Section: Non-tryptaminesmentioning
confidence: 99%
“…In one particularly active branch of such labelling research, hydrogen isotope exchange (HIE) is employed to deliver either deuterium or radioactive tritium to pharmaceutical drug candidates in one synthetic step. As well as circumventing the requirement for isotopically-enriched starting materials in preparing tritiated drug candidates [1,5], HIE can also provide analogous deuterated compounds for use as internal standards for mass spectrometry [11,12], for kinetic isotope studies [13,14], and for the alteration of reaction pathways in total synthesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The strategic use of deuterium minimized an undesirable competitive reaction, thus giving synthetically useful yields of the desired insertion product 289. 56 delivered tetrahydrofuran 292 (Scheme 53). 56,57 In previous studies, it was found that TBAF/air can facilitate C-3 oxidation of oxindoles containing the welwitindolinone scaffold, but the use of TBAF/air to build an ethereal linkage through double C-H functionalization was unknown.…”
Section: Synthesis Of (-)-N-methylwelwitindolinone C Isothiocyanatementioning
confidence: 99%
“…56 delivered tetrahydrofuran 292 (Scheme 53). 56,57 In previous studies, it was found that TBAF/air can facilitate C-3 oxidation of oxindoles containing the welwitindolinone scaffold, but the use of TBAF/air to build an ethereal linkage through double C-H functionalization was unknown. 58a,b Notably, the use of other bases in place of TBAF, such as K 2 CO 3 and Cs 2 CO 3 , also promoted the formation of 292, albeit in lower yields.…”
Section: Synthesis Of (-)-N-methylwelwitindolinone C Isothiocyanatementioning
confidence: 99%